Influências da psicanálise na constituição da Psicologia Política: Reich, Fromm e Adorno - Richter, Ernesto Pacheco (2017)
This work aims to analyze the influences of psychoanalytic theory in the process of constitution of Political Psychology, as research field. Initially, we focus on French authors, such as, Alexis de Tocqueville, Gabriel Tarde and Gustave Le Bon, whose contributions regarding French revolutions are relevant to the field. On the other hand, we present the Anglophone authors Graham Wallas and Harold Lasswell, as their thoughts bring different perspectives to political events, but no less significant for the later institutionalization of Political Psychology. Afterwards, we analyze Freud’s social texts, as well as the metapsychological ones, in order to elucidate the political elements underlying psychoanalytic theory. Finally, we present three authors we consider essential to the history of the field: Wilhelm Reich, Erich Fromm and Theodor Adorno, whose main interest was the study of authoritarianism. Through a critical and reflexive analysis, we show the contributions of psychoanalysis and how it was appropriated by these authors. This research is justified by filling a gap in the history of Political Psychology, and showing the relevance that psychoanalysis has had for political thought, especially during and shortly after World War II. Furthermore, the contributions of these authors are undoubtedly present, given the growing adherence to the authoritarian discourse observed in the 21st century